2021
DOI: 10.1158/1535-7163.mct-20-1132
|View full text |Cite
|
Sign up to set email alerts
|

Multimeric Anti-DR5 IgM Agonist Antibody IGM-8444 Is a Potent Inducer of Cancer Cell Apoptosis and Synergizes with Chemotherapy and BCL-2 Inhibitor ABT-199

Abstract: Death receptor 5 (DR5) is an attractive target for cancer therapy due to its broad upregulated expression in multiple cancers and ability to directly induce apoptosis. Though anti-DR5 IgG antibodies have been evaluated in clinical trials, limited efficacy has been attributed to insufficient receptor crosslinking. IGM-8444 is an engineered, multivalent agonistic IgM antibody with 10 binding sites to DR5 that induces cancer cell apoptosis through efficient DR5 multimerization. IGM-8444 bound to DR5 with high avi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Finally, IGM-8444 is an IgG DR5 antibody. With 10 binding units, it is capable of binding multiple receptors at once, facilitating receptor clustering [ 62 ]. IGM-8444 was found to induce apoptosis in a broad panel of solid and hematological malignancies [ 62 ].…”
Section: Improving Upon Trail Receptor-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, IGM-8444 is an IgG DR5 antibody. With 10 binding units, it is capable of binding multiple receptors at once, facilitating receptor clustering [ 62 ]. IGM-8444 was found to induce apoptosis in a broad panel of solid and hematological malignancies [ 62 ].…”
Section: Improving Upon Trail Receptor-based Therapiesmentioning
confidence: 99%
“…With 10 binding units, it is capable of binding multiple receptors at once, facilitating receptor clustering [ 62 ]. IGM-8444 was found to induce apoptosis in a broad panel of solid and hematological malignancies [ 62 ]. A phase I study is currently recruiting patients to test IGM-8444 alone and in combination in subjects with cancer (NCT04553692).…”
Section: Improving Upon Trail Receptor-based Therapiesmentioning
confidence: 99%
“…In particular, VDAC2 plays a role both in recruiting BAK to the MOM and in inhibiting its activation [17] . WEHI-9625 is a novel small molecule inducing BAK-mediated apoptosis in mice but is completely inactive against human BAK [87,88] . We found that ironomycin sequestered iron into lysosomes and subsequently reduced mitochondrial iron load, promoting the recruitment and non-canonical activation of BAX/BAK in AML in vitro and in vivo models.…”
Section: Apoptotic Inducersmentioning
confidence: 99%
“…Agonists of the TNF-related apoptosis-inducing ligand (TRAIL) receptors (DR4/5) have been tested in AML, but response rates are low [ 13 ] . Novel antibodies against TRAILR1 and TRAILR2 have shown promising preclinical data along with synergy with VEN and are currently tested in phase 1 [ Table 2 ] [ 89 ] . Eftozanermin alfa (ABBV-621), a second-generation TRAIL receptor agonist binding to the death-inducing DR4 and DR5 receptors, is currently being tested in solid tumors and hematological malignancies [ Table 2 ] [ 90 , 91 ] .…”
Section: Rcd Inducers In Amlmentioning
confidence: 99%
“…Among those, biologics assembled based on IgM 33 , synthetic nanocages 34 and Minibinder 35 formats have demonstrated superior neutralization properties against SARS-CoV-2 compared to conventional mAb formats. Additionally, the avid molecules GEN3009 35 , INBRX-106(Inhibrx) 36 and IGM-8444 37 are being tested in Phase I/II clinical trials for the treatment of hematological and solid tumors, highlighting the clinical benefit of multivalent antibody-presenting formats. Following a similar principle, but using the human light-chain apoferritin protomer to drive oligomerization of antibody fragments, we developed a platform called the Multabody (MB) to increase neutralization potency of antibodies targeting SARS-CoV-2 38 and HIV-1 39 .…”
Section: Introductionmentioning
confidence: 99%